Second-harmonic generation in quaternary atomically thin layered AgInP2S6 crystals - Wang, Xingzhi (2020)
Nonlinear effects in two-dimensional (2D) atomic layered materials have attracted increasing interest. Here, we report the observation of optical second-harmonic generation (SHG) in two-dimensional atomically thin silver indium phosphorus sulfide (AgInP2S6) crystals, with odd layer thickness. The nonlinear signal facilitates the use of thickness-dependent SHG intensity to investigate the stacking type of this material, while the crystal-orientation dependent SHG intensity of the monolayer sample reveals the rotational symmetry of the AgInP2S6 lattice in plane. Our studies expand the 2D crystal family in nonlinear effect field, which opened considerable promise to the functionalities and potential applications of 2D materials.